Boom aurifère et dynamiques économiques entre Sénégal, Mali et Guinée - Faty B. Mbodj (EchoGéo)
The mining reforms undertaken by countries like Guinea (1995), Mali (1999) and Senegal (2003) have created favorable conditions for the investment of gold multinationals in a transborder area located between the east of Senegal, the west of Mali and the north-east of Guinea. Through the side activities and direct investments brought about, these firms appear as an opportunity to integrate these marginalized zones within the national and regional economies. However, their financial contributions are insufficient and they provoke direct and indirect competition on local agricultural economies, raising questions on the role of extractive activities for the economic future of the areas studied.